THE INFLUENCE OF DIGITAL MARKETING, ELECTRONIC WORD OF MOUTH (E-WOM) AND PRICING ON PURCHASING DECISIONS(Study of Tokopedia Consumers in Denpasar City) - Dico Rizky Izulhaq; I Made Jatra (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Purchasing decisions are a series of processes that start with customers identifying a problem, looking for information regarding a particular brand or product, and evaluating the brand or product to see how well existing alternatives can solve the problem. There are several factors that influence purchasing decisions, including digital marketing, Electronic Word of Mouth (E-WOM) and price. This research aims to explain the influence of digital marketing, E-WOM and price on purchasing decisions simultaneously or partially. The population in this research is all Tokopedia E-commerce consumers in Denpasar City, the exact number of which is not known. The number of samples used in this research was 112 respondents. The sampling method used in this research is a non- probability sampling method with a purposive sampling technique. Data collection was carried out by distributing questionnaires online via Google Form. The data analysis technique used in this research is multiple linear regression analysis with the help of the SPSS 26 application. The results of this research show that digital marketing has a positive and significant effect on purchasing decisions, E-WOM has a positive and significant effect on purchasing decisions and price has a positive effect. positive and significant on purchasing decisions. The theoretical implications of this research provide support for consumer behavior theory and expand empirical knowledge regarding digital marketing, E-WOM, prices and purchasing decisions. Practically, it is hoped that Tokopedia will provide consideration regarding the importance of online marketing systems, E-WOM and prices in Tokopedia's marketing strategy to improve consumer purchasing decisions.